Epidemiology and impact of HIV-HBV co-infection on haemato-biochemical parameters in patients at the Matam Community Medical Centre (City of Conakry) - Camara, Taliby Dos; Makanera, Abdoulaye; Sy, Mariam Bailo; Diallo, Fatimatou (The Asia Journal of Applied Microbiology, 2023)
The human immunodeficiency virus (HIV) and hepatitis B virus (HBV) co-infection is a major public health problem wordlwide. The aim was to determine the impact of HIV/HBV co-infection on haemato-biochemical parameters in 400 patients, from July 1st to October 30th, 2022 at the Matam Medical communical center (MMC), in Conakry. The results showed that positivity was 12.5% for HIV, 12% for HBV and 4% for HIV/HBV coinfection. For hematological parameters, 81% (13/16) of HIV/HBV coinfected patients had low hemoglobin levels, with frustrated anaemia (54%), moderate anaemia (15%), severe anaemia (31%), microcytic anaemia (23%), normocytic anaemia (77%), hypochromic anaemia ‘8%), normochromic anaemia (92%), hyponeutrophilia (31%), red blood cell (19%). With monocyte values, 31% had hyperlymphocytosis, 19% had hypermonocytosis and 12% had hypereosinophilia. For biochemical parameters, 69% and 56% of coinfected patients had abnormal increased values of Alanine Aminotransferse (ALT) levels, Aspartate Aminotransferase (AST) levels. In relation to the epidemiological variables, Female was the most represented with 56%, all age groups are almost affected with the majority between 21-40 years, 56% followed by 41-60 years with 25% and ≤ 20 years with 19%. Married people are more represented by infections with 56% followed by Singles with 31% and Widows 13%. Almost all socio-professional categories are affected by infections with a high seroprevalence among Housewives, Commercial Agents and Workers with 25%, followed by Pupils/Students with 19% and Administrative Agents with 6%. These results showed that HIV/HBV co-infection had negative impact on hemato-biomedical parameters of the majority of patients in the present studies.